PENATALAKSANAAN FISIOTERAPI PADA KONDISI PIRIFORMIS SYNDROME DEKSTRA DENGAN MODALITAS TENS, FRICTION DAN METODE TERAPI LATIHAN DI RSUD BENDAN - Bayu Aji; Eko Budi Prasetyo (LPPM Universitas Pekalongan, 2018)
Piriformis syndrome is a reversible compression of sciatic nerve by piriformis muscle. This condition can cause deep and intense pain in the buttocks, hip, and sciatica, with radiation of pain towards the thighs, legs, feet and toes, painful symptoms in the buttocks, especially in the piriformis muscle area, increased pain after sitting in time 15-20 minutes, sometimes with difficulty walking, and pain during internal hip rotation. Factors that influence the primary andsecondaryfactors.To determine the effect of physiotherapy management in reducing pain, spasm, increased muscle strength, and functional activity in the right cerebral palsy syndrome condition using the tens, friction, and exercise modalities.Keywords: right piriformis syndrome, tens, friction and exercise therapy